2014
DOI: 10.1353/hpu.2014.0079
|View full text |Cite
|
Sign up to set email alerts
|

A Qualitative Study of Pregnancy Intention and the Use of Contraception among Homeless Women with Children

Abstract: We undertook a qualitative analysis informed by grounded theory to explore pregnancy intention and the barriers to contraceptive use as perceived by homeless women with children. Semi-structured interviews (n = 22) were performed in English and in Spanish. The dominant theme emerging from the interviews was a strong desire to avoid pregnancy while homeless. However, few women in our sample used contraception or accessed reproductive health care consistently. There were multiple barriers to using contraception … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
121
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(126 citation statements)
references
References 31 publications
1
121
0
3
Order By: Relevance
“…1 Unfortunately, Veterans are four times more likely to experience homelessness than civilians and, consequently by default, the VHA has become the largest U.S. homeless healthcare provider. 2,3 Providing medical care to Veterans experiencing homelessness is resource intensive due to a high prevalence of chronic health conditions in this population 4 and homeless women have additional, though preventable, reproductive health risks 5 . Access to gender-specific services, including preconception planning, pregnancy-related care, and contraceptive management varies by location in VHA facilities due to availability of subject matter expertise and comfort level of providers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Unfortunately, Veterans are four times more likely to experience homelessness than civilians and, consequently by default, the VHA has become the largest U.S. homeless healthcare provider. 2,3 Providing medical care to Veterans experiencing homelessness is resource intensive due to a high prevalence of chronic health conditions in this population 4 and homeless women have additional, though preventable, reproductive health risks 5 . Access to gender-specific services, including preconception planning, pregnancy-related care, and contraceptive management varies by location in VHA facilities due to availability of subject matter expertise and comfort level of providers.…”
Section: Introductionmentioning
confidence: 99%
“…8 Unfortunately, homeless women have low contraceptive utilization, are at high risk for sexual exploitation, and face challenges prioritizing reproductive health care due to competing demands in their high-stress environment. 5,9 One study of homeless women Veterans found approximately 30% already have minor children in their custody and 11% have psychotic disorders. 10 Additional pregnancies, especially unintended, could further destabilize an already fragile family structure.…”
Section: Introductionmentioning
confidence: 99%
“…The subjectivity of current or future motherhood was identified in 5 studies . The importance of preserving or safeguarding future fertility was identified as a barrier or concern related to hormonal contraception.…”
Section: Resultsmentioning
confidence: 99%
“…A lack of control or invisibility of identity was noted in 3 studies . Women who were currently homeless saw themselves as less free to make their preferred contraceptive decisions, in part because of the overwhelming necessity of tending to more pressing and important needs such as food and shelter . Women with a history of childhood sexual abuse were more likely to report feeling hopeless, insecure, or undeserved.…”
Section: Resultsmentioning
confidence: 99%
“…And so if I have to just eliminate a couple of things just to keep my mind focused—children got to school, okay, I might have to go to work, I’m trying to get this housing…you can’t stop to take care of your health sometimes. So it’s very, very, very hard.” 30 Without this understanding of low-income housed and homeless women’s lived experiences gleaned through qualitative inquiry, the implementation of gynecologic and other healthcare which ignored the unique needs of this population would likely prove ineffective.…”
Section: Low Socioeconomic Statusmentioning
confidence: 99%